المجتمع التقليدي وصناعة الفحل الماورائي من خلال قصة (قبّة سيدي عبد المالك) لـ: محمد الصدّيق معوش. (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص:   تقدّمُ هذه الورقة تصوّراً جديداً عن فكرة الفحل الثقافي غير تلك الصورة التي سوّقها الغذامي في النقد الثقافي عن الفحل المتشعرن. إنّه الفحل الماورائي الذي يثبت ويترسّخ مدعوما بقيم وثقافة المجتمع التقليدي.  ومن خلال قصة(قبّة سيدي عبد المالك) –موضوع الدّراسة-للكاتب محمّد الصدّيق معوش، سنرى كيف يتحوّل صاحب هذه القبّة إلى فحلٍ ماورائيٍّ يمارس فحولته ميّتاً كما مارسها حيّاً. كلمات دالة : فحولة، مجتمع، تقليدي، نسق، ثقافة، ماورائي.  Abstract      This paper presents a new conception of the idea of the cultural stallion, other than the image promoted by Al-Ghadami in the cultural criticism of the hairy stallion. It is the metaphysical stallion that is established and entrenched, supported by the values and culture of traditional society.      Through the story (The Dome of Sidi Abdel Malik) - the subject of the study - by the writer Muhammad Al-Siddiq Ma'ouch, we will see how the owner of this dome turns into a metaphysical stallion practicing his virility dead as he practiced it alive.Keyword: virility, society, traditional, style, culture, metaphysics.